Faktor Faktor yang Mempengaruhi Gen Z di Universitas Dian Nuswantoro dalam Penggunaan Pinjaman Online - Klarisa Widiana Pratiwi; Ariati Anomsari; Dwi Eko Waluyo; Fakhmi Zakaria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of financial technology has driven the increasing use of online loans among Generation Z, who are adaptable to technology and have a digital lifestyle. This study aims to analyze the influence of perceived ease of use, lifestyle, and trust on the interest in using online loans among students at Dian Nuswantoro University. The approach used was quantitative with a purposive sampling technique on respondents aged 18–26 who had used online loans in the past six months. Data were collected through a Likert-scale questionnaire and analyzed using PLS-SEM assisted by SmartPLS. The results showed that all variables had a positive and significant effect on interest in use, with lifestyle being the most dominant factor, followed by trust and perceived ease of use. These findings indicate that Generation Z's interest is driven not only by technical aspects, but also by lifestyle and confidence in the security of services. Therefore, increasing financial literacy is needed to make the use of online loans more prudent.